A representação literária da educação brasileira na transição do século XIX para o século XX : a perspectiva de José Lins do Rêgo - Carlos, Erika Michela (Universidade Federal de São Carlos, 2009)
This study is about the literary works by José Lins do Rêgo. Its objective is to apprehend the Brazilian society at the transition moment between the 19th and 20th centuries. As a consequence, it also reveals the author s view regarding education in Brasil, which the author had access to. The Literature was approached as an auxiliary source to the History of Education, with the intention of interpreting and explaining the multiple and complex expressions that resulted from the dialectic interactions and educational actions and Brazilian society. Therefore the literary works by José Lins do Rêgo are part of the primary sources, more specifically those that belong to the Sugar Cane Cycle - Ciclo da Canade- Açúcar: Menino de engenho, Doidinho, Banguê, O moleque Ricardo, Usina and Fogo morto. Due to the fact that theses literary works present particular potential for the study of the history of Brazilian education the choice is justified. Some extracts were selected, which portray the thematic Brazilian education in the transition between centuries. These extracts were analyzed considering as reference educational historiographical works. Such analysis was based on a Marxist view where the social environment and textual structure influence each other in constructing the works in a dialectic movement which understand art and society. It was possible to conclude through research that a negative view of education can be perceived: elitist education, reserved only for the sons of the elite, which excluded the poor boys and girls. The ladies from the elite were educated to guarantee social attributes, which prepared them to take on a social function, that is, to be wives and mothers. Therefore, José Lins do Rêgo presents a posthumous perspective of the Brazilian education within the context studied, which seems to be influenced by demands of changes in the school. This period is marked by other aspects, such as the emergence of the Manifest - Manifesto dos Pioneiros da Escola Nova.
Keywords: Educação - história; Literatura brasileira; Rêgo, José Lins do, 1901-1957; Brazilian history of education; Literature; José Lins do Rêgo; CIENCIAS HUMANAS::EDUCACAO